2015
DOI: 10.1097/spv.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Intra-Abdominal Pressure Measured During Physical Activities Via a Wireless Vaginal Transducer

Abstract: Aims In the urodynamics laboratory setting, a wireless pressure transducer, developed to facilitate research exploring intra-abdominal pressure (IAP) and pelvic floor disorders, was highly accurate. We aimed to study reproducibility of IAP measured using this transducer in women during activities performed in an exercise science laboratory. Methods Fifty seven women (mean ± SD: age 30.4 ±9.3 years; body mass index=22.4 ± 2.68 kg/m2) completed two standardized activity sessions using the same transducer at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In previous work, we found that activities with higher maximal IAP tended to have greater variability between two sessions, though very few activities demonstrated a statistically significant difference in mean maximal IAP between sessions. [20] However, in two activities similar to that performed for the current study, the absolute limits of agreement for net mean maximal IAP were 5.6 cm H 2 O for walking 4.8 km/hr at 0% grade and 11.5 cm H 2 O for walking 4.3 km/hr at 0% grade carrying an 11.4 kg weight. If reproducibility is similar between conducting these activities on a treadmill versus a track (as in the current study), the differences seen between activities overcome the inherent test-retest variability of the measures.…”
Section: Discussionmentioning
confidence: 47%
“…In previous work, we found that activities with higher maximal IAP tended to have greater variability between two sessions, though very few activities demonstrated a statistically significant difference in mean maximal IAP between sessions. [20] However, in two activities similar to that performed for the current study, the absolute limits of agreement for net mean maximal IAP were 5.6 cm H 2 O for walking 4.8 km/hr at 0% grade and 11.5 cm H 2 O for walking 4.3 km/hr at 0% grade carrying an 11.4 kg weight. If reproducibility is similar between conducting these activities on a treadmill versus a track (as in the current study), the differences seen between activities overcome the inherent test-retest variability of the measures.…”
Section: Discussionmentioning
confidence: 47%
“…10 In another study of 51 predominantly nulliparous women, Curl-up maximal IAP mean value was 22.1 cm H 2 O while it was 100.2 cm H 2 O during cough. 13 The IAP increase during Curl-up appears thus to be much lower than during coughing. In addition, an electromyographic activation of 44% of maximal voluntary contraction (MVC) of the pelvic floor muscles during Curl-up was measured by Neumann et al 15 in four nulliparous women.…”
Section: Introductionmentioning
confidence: 91%
“…[6][7][8] IAP during exercises is most often measured using vaginal or rectal sensor. [9][10][11][12] Coughing, Valsalva maneuver, and jumping have been described as the most hyperpressive exercises 9,13 and are avoided as much as possible in post-partum.…”
Section: Introductionmentioning
confidence: 99%
“…The abdominal pressure loading was placed perpendicular to the AVW. In all simulations in this study, the Valsalva (increasing in abdominal pressure loading) was simulated using 20 increments in pressure from 0 to 100 cmH 2 O, with the maximum Valsalva pressure close to the average laying Valsalva pressure measured using a vagina pressure sensor [37]. To reduce computation time, the simulated Valsalva process was scaled to 1 s.…”
Section: Generate Specific Finite-element Model Input Files With Desired Geometry Materials Property and Loading Conditionmentioning
confidence: 99%